Speaking Christian : why Christian words have lost their meaning and power-- and how they can be restored - Borg, Marcus J. (HarperOne, 2011)
Asserts that a failure to understand Christian words and phrases has lead to the religion losing much of its meaning, and offers a path back to a true understanding of Christianity.